Feasibility study for the implementation of number portability in Nicaragua - Guillermo de Jesús Valdivia-Medina (Tecnología en Marcha)
The document “Feasibility Study for the Implementation of Number Portability in Nicaragua” proposes the mechanisms to implement operator Number Portability, taking into account the ITU-T Series Q and E regulations. The existing information is analyzed, after the collection of information through interviews with operator officials, as well as surveys of users of telephone services. After reviewing the advantages and conditions of the different techniques to implement number portability, we recommend the All Call Query technique, a simple and effective method, as well as operator Number Portability, for which you need intelligent network capabilities to recognize the ported number, the status, the conditions and the operator must develop activities to adapt their networks to this model. The documents that legally and regulatory support the implementation of Number Portability are: Administrative Agreement No. 036-2003, the Numbering Resource Regulations and the National Numbering Plan, all of these issued by TELCOR Regulatory Entity, the Free Trade Agreement between the Dominican Republic - Central America and the United States (DR-CAFTA) and the Regional Technical Telecommunications Commission of Central America, COMTELCA The elaboration of regulatory documents such as the Number Portability Regulation is proposed and indications are given for the creation of the Centralized Database Administrator with its subordinates in the different nodes that make up the network and a proposal for a General Implementation Plan.